Ethics and the Special Education Assistant - Birkeland, Lise (Paideusis)

(untitled) (Canadian Philosophy of Education Society, 2008)
The need for and responsibilities of Special Education Assistants (also known as Teacher Assistants, Teacher Aides, and Education Assistants) in British Columbia are increasing; yet time to consult, plan and receive direction is decreasing due to teachers’ burgeoning workloads and time constraints. Coupled with the fact that SEA’s often have more specific knowledge of the student’s label and educational interventions, these dynamics sometimes create a climate of misunderstanding and confusion of the roles and responsibilities of teachers and their assistants. At times, SEA’s feel unsupported and forced to take on responsibility without authority as they navigate through the ethics of what is the best inclusive practice for the student with special needs. By using an ethical approach to analyze an example of a) the Special Education Assistant’s working life and b) one extreme experience of that life, insight into the varied nature of this world is illuminated.